Therapeutic platelet transfusion versus routine prophylactic transfusion in patients with haematological malignancies: an open-label, multicentre, randomised study - Wandt, Hannes; Thalheimer, Markus; Mahlknecht, Ulrich Rudolph; Ho, Anthony Dick (The lancet, 2012)
Summary - Background - Routine prophylactic platelet transfusion is the standard of care for patients with severe thrombocytopenia. We assessed the effect of a new strategy of therapeutic platelet transfusion on the number of transfusions and safety in patients with hypoproliferative thrombocytopenia. - Methods - We did a multicentre, open-label, randomised parallel-group trial at eight haematology centres in Germany. Patients aged 16-80 years, who were undergoing intensive chemotherapy for acute myeloid leukaemia or autologous haemopoietic stem-cell transplantation for haematological cancers, were randomly assigned via a computer-generated randomisation sequence to receive either platelet transfusion when bleeding occurred (therapeutic strategy) or when morning platelet counts were 10×109 per L or lower (prophylactic strategy). Investigators undertaking interventions were not masked to group assignment. The primary endpoint was the number of platelet transfusions. Analysis was by intention to treat. This trial is registered, NCT00521664. - Findings - 197 patients were assigned the prophylactic strategy and 199 the therapeutic strategy. Of 391 patients analysed, the therapeutic strategy reduced the mean number of platelet transfusions by 33·5% (95% CI 22·2-43·1; p<0·0001) in all patients (2·44 [2·22-2·67] in prophylactic group vs 1·63 [1·42-1·83] in therapeutic group), 31·6% (18·6-42·6; p<0·0001) in those with acute myeloid leukaemia (2·68 [2·35-3·01] vs 1·83 [1·58-2·10]), and 34·2% (6·6-53·7; p=0·0193) in those who had had autologous transplantation (1·80 [1·45-2·15] vs 1·18 [0·82-1·55]. We noted no increased risk of major haemorrhage in patients who had undergone autologous transplantation. In those with acute myeloid leukaemia, risk of non-fatal grade 4 (mostly CNS) bleeding was increased. We recorded 15 cases of non-fatal haemorrhage: four retinal in each transfusion group, and one vaginal and six cerebral in the therapeutic group. 12 patients died in the study: two from fatal cerebral haemorrhages in the therapeutic group, and ten (five in each treatment group) unrelated to major bleeding. - Interpretation - The therapeutic strategy could become a new standard of care after autologous stem-cell transplantation; however, prophylactic platelet transfusion should remain the standard for patients with acute myeloid leukaemia. The new strategy should be used by some haematology centres only if the staff are well educated and experienced in the new approach and can react in a timely way to first signs of CNS bleeding. - Funding - Deutsche Krebshilfe eV (German Cancer Aid).